Synthesis of Ag3PO4 using Hydrophylic Polymer and Their Photocatalytic Activities under Visible Light Irradiation - Uyi Sulaeman; Bin Liu; Shu Yin; Tsugio Sato (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
The highly active Ag3PO4 photocatalysts were successfully synthesized using the hydrophylic polymer of PVA (polyvinyl alcohol), PEG (polyethylene glycol) and PVP (polyvinyl pyrrolidone). The products were characterized using X-ray diffraction (XRD), Diffuse reflection spectroscopy (DRS), Field emission scanning electron microscope (FE-SEM), Brunauer–Emmett–Teller (BET) specific surface area, and X-ray photoelectron spectroscopy (XPS). Photocatalytic activities were evaluated using decomposition of Rhodamine B (RhB) under visible light irradiation. The results showed that the PVA, PEG, and PVP increased the specific surface area and enhanced the photocatalytic activity of Ag3PO4. The highest photocatalytic activity could be observed in Ag3PO4 synthesized with PVA, mainly due to an increase in electron excitation induced by PVA chemically adsorbed on the surface.